2018
DOI: 10.1108/he-07-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

School and emotional well-being: a transcultural analysis on youth in Southern Spain

Abstract: Purpose The purpose of this paper is to assess and compare school well-being (SW) and emotional well-being (EW) among Romanian, Moroccan and Spanish youth, to determine the degree of relation between EW and scholar well-being. Design/methodology/approach The paper employed cross-sectional research with cluster sampling in two primary schools and seven secondary schools. The questionnaire Kidscreen-27 was distributed to a sample of 1,840 Romanian, Moroccan and Spanish students aged between 10 and 19 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
(45 reference statements)
0
10
1
3
Order By: Relevance
“…Various studies have reported immigrant youth in some populations having higher levels of well‐being than their native peers, in terms of low stress, positive emotions, and self‐esteem (Dimitrova, 2011; Güngör & Perdu, 2017; Sam, Vedder, Liebkind, Neto, & Virta, 2008; Van Geel & Vedder, 2010). Although in our study we found lower positive affect in the first‐generation immigrant students than their native peers, and also lower levels in the first‐generation immigrant students that the group of second‐generation immigrants (Borraccino et al, 2018; OECD, 2016; Soriano & Cala, 2018). Particular note should be taken of these results, as indicators of positive affect such as happiness and cheerfulness have been positively associated with motivation, self‐efficacy, school engagement, and ultimately with academic performance (King, McInerney, Ganotice, & Villarosa, 2015; Mega, Ronconi, & De Beni, 2014; Pekrun, Goetz, Titz, & Perry, 2002; Weber et al, 2016).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Various studies have reported immigrant youth in some populations having higher levels of well‐being than their native peers, in terms of low stress, positive emotions, and self‐esteem (Dimitrova, 2011; Güngör & Perdu, 2017; Sam, Vedder, Liebkind, Neto, & Virta, 2008; Van Geel & Vedder, 2010). Although in our study we found lower positive affect in the first‐generation immigrant students than their native peers, and also lower levels in the first‐generation immigrant students that the group of second‐generation immigrants (Borraccino et al, 2018; OECD, 2016; Soriano & Cala, 2018). Particular note should be taken of these results, as indicators of positive affect such as happiness and cheerfulness have been positively associated with motivation, self‐efficacy, school engagement, and ultimately with academic performance (King, McInerney, Ganotice, & Villarosa, 2015; Mega, Ronconi, & De Beni, 2014; Pekrun, Goetz, Titz, & Perry, 2002; Weber et al, 2016).…”
Section: Discussioncontrasting
confidence: 66%
“…It is evident that research should be encouraged which examines the inluence or mediating effect of a mix of socioeconomic and sociodemographic variables, including the students' countries of origin (Borraccino et al, 2018;Soriano & Cala, 2018), their age at arrival in their adopted country (Bausela-Herreras, 2017), native languages, teacher training, and the readiness of education systems (Esteban, 2019). These variables may help us to explain the differences found between native and immigrant students.…”
Section: Tablementioning
confidence: 99%
“…Education is perceived as the basis for the acquisition of skills and knowledge and is therefore an important facilitator of a migrant's future economic inclusion and upward mobility. Schools are also seen as having a role in responding to the needs of migrants in terms of their well-being, language acquisition, and the development of relationships with peers and teachers (Due et al 2015;Soriano & Cala, 2018), providing a safe and stable environment for refugee children (Aydin et al, 2019;Block et al, 2014;Seker & Sirkeci, 2015) and a place where discrimination, racism, and stigmatization can be actively countered (Medari c & Sedmak, 2012). However, studies also emphasize that teachers are not immune to various forms of stereotyping; while they do not necessarily overtly express negative attitudes towards migrants, ethnic stereotypes and prejudices manifest themselves in many different forms (Tenenbaum & Ruck, 2007), which can lead to migrant children achieving lower grades and leaving school sooner than their non-migrant peers (de Heer et al, 2015;Katz & Isik-Ercan 2015;Pugh et al, 2012).…”
Section: The Integration Of Migrant Children As a Social Processmentioning
confidence: 99%
“…En el terreno de la educación, el bienestar subjetivo podría plantearse como una meta educativa, la cual se tendría que enmarcar en las condiciones éticas de la sociedad o incluso rasgos culturales, en los que se identifican los aspectos positivos y fortalezas (Soriano y Cala, 2018). Ante esta posibilidad, es importante señalar que las emociones en el contexto educativo no pueden mantener el valor otorgado por la teoría del bienestar subjetivo, ya que lo positivo y negativo no estaría únicamente determinado por lo que siente el sujeto, sino por normas objetivas fundadas en la moral.…”
Section: El Bienestar Y Las Emociones En La Educaciónunclassified